RETRACTED: ADOLESCENT-PARENT COMMUNICATION ON SEXUAL AND REPRODUCTIVE HEALTH AND ITS ASSOCIATED FACTORS AMONG HIGHER SECONDARY SCHOOL STUDENTS OF TOKHA MUNICIPALITY, NEPAL : A CROSS-SECTIONAL STUDY - Gautam , Alisha; Sharma, Krishna; Dhakal, Sunita; Dhakal, Sarmila; Chand , Anugraha (Fakultas Ilmu Kesehatan, Kedokteran dan Ilmu Alam (FIKKIA), Universitas Airlangga, 2023)
Referred to by: RETRACTION NOTICE TO “ADOLESCENT-PARENT COMMUNICATION ON SEXUAL AND REPRODUCTIVE HEALTH AND ITS ASSOCIATED FACTORS AMONG HIGHER SECONDARY SCHOOL STUDENTS OF TOKHA MUNICIPALITY, NEPAL: A CROSS-SECTIONAL STUDY” (JOURNAL OF PUBLIC HEALTH RESEARCH AND COMMUNITY HEALTH DEVELOPMENT, VOL. 7 NO. 1 (2023): OCTOBER) This article has been retracted: please see Journal of Public Health Research and Community Health Development Publication Ethic (https://e-journal.unair.ac.id/JPHRECODE/Editorial_Policies#custom-2). This article has been retracted at the request of the Editor-in Chief. The author has done double publication in the following journal. Gautam, A., Sharma, K., Dhakal, S., Dhakal, S., & Chand, A. 2022. Adolescent-Parent Communication on Sexual and Re-productive Health and its Associated Factors among Higher Secondary School Students of Tokha Municipality, Kathmandu, Nepal. Journal of Public Health International, 6(2), 1–15. https://doi.org/https://doi.org/10.14302/issn.2641-4538.jphi-22-4332 One of the requirements for submitting a manuscript for publication is that the author must state explicitly that their work is original and has never been published or submitted in other journals until there is a decision from JPH RECODE regarding the status of the manuscript. Therefore, this article is a serious abuse of the scientific publishing system. The scientific community strongly opposes this, and we apologize to the journal readers that this was not detected during the publication process.